Degradation of p-cresol in the presence of UV light driven in an integrated system containing photocatalytic and packed bed biofilm reactor - Kumar Jaiswal V.; Dutta Gupta A.; Verma V.; Sharan Singh R. (My University, 2025)
Integrating photocatalysis and biodegradation has shown great potential in wastewater treatment technology. In this study, the degradation of p-cresol in water has been investigated through an integrated system comprising of photocatalytic and packed bed biofilm reactor (PBBR). In the photocatalytic reactor, the biodegradability index (BOD5/COD, BOD5/TOC) of the p-cresol solution was first shown to increase (from 0.098±0.023 to 0.59±0.089 for BOD5/COD and from 0.27±0.030 to 1.74±0.03 for BOD5/TOC). The pseudo-first-order rate constant (kap) was found to be 0.011 min−1. The % removal of the integrated system was found to be 98.43±1.31% at an initial concentration of 700 mg L-1 and residence time of 120 h, which was significantly higher than the PBBR operated alone (34.82±2.62%) under optimized conditions (pH 7.0 and T = 32±2 °C). Using an integrated approach, the efficient removal of p-cresol opens novel future perspectives for catalytic degradation using chemical oxidation. © 2023